Un « nouvel Alexandre » mamelouk, al-Malik al-Ashraf Khalïl et le regain eschatologique du XIIIe siècle - François de Polignac (Revue des Mondes Musulmans et de la Méditerranée)
In the long inscription that runs above the main entrance of thefortress in Aleppo, the Mamluk sultan al-Malik al-Ashraf Khalil (689/1290-692/1294) is called “the Alexander of his time”. Though he was neither the first nor the only Mamluk sovereign to use this title (Baybars apparently first introduced it), al-Malik al-Ashraf gave it a specific meaning inspired by his own military successes and his hopes of recovering the lands seized by the Mongols in 1258. The Mongol kings of the Ilkhan dynasty who reigned over Persia and Irak would themselves be compared with Alexander in the early 14th century, but their claim was inspired by the legends which, since Ferdowsi's Shàh-nâma, had reshaped the Macedonian king into the figure of a national hero. The Alexander whom al-Malik al-Ashraf was referring to was closer to the inspired “He with the double horn” (Dhü l-Qarnayn) of the Coran, who had built the wall enclosing the wicked tribes of Gog and Magog until the Judgment-day. Thus, the victorious sultan who was preparing to expel from Irak the Mongols assimilated to Gog and Magog, and to reestablish the Abbassid califate in Bagdad, could give the dimension of eschatology to his deeds and appear both as a universal conqueror and the founder of a new era of islam.